Hepatitis C Virus; Its Implication for Endodontists - Mahboobi, Nima; Mahboobi, Nastaran; Oliaei, Parvin; Alavian, Seyed Moayyed (Iranian Endodontic Journal, 2014)
Over 170 million patients worldwide are chronically infected with Hepatitis C virus (HCV); making it a globally important infection. Dentists constantly handle sharp instruments infected with biological fluids and are therefore considered at high-risk of contracting HCV infection. Needle-stick injuries seem to be the most common route of exposure to blood-borne pathogens in dental practice. Moreover, endodontist’s constant use of sharp instruments such as endodontic files with limited operative vision in a small working field (i.e. root canal system) increases their risk of exposure to infection. The aim of this study was to review the epidemiology of HCV infection in dental healthcare staff and the tests required for its diagnosis. We also look at the protocols for dental treatment in infected individuals and screening and dental examination tailored for HCV patients.